2009
DOI: 10.1038/cdd.2009.113
|View full text |Cite
|
Sign up to set email alerts
|

Kv1.1 and Kv1.3 channels contribute to the degeneration of retinal ganglion cells after optic nerve transection in vivo

Abstract: Degeneration of retinal ganglion cells (RGCs) -an important cause of visual impairment -is often modeled by optic nerve transection, which leads to apoptotic death of these central nervous system neurons. With this model, we show that specific voltage-gated K þ channels (Kv1 family) contribute to the degeneration of rat RGCs and expression of apoptosis-related molecules in vivo. Retinal expression of Kv1.1, Kv1.2, Kv1.3 and Kv1.5 was examined by quantitative real-time reverse transcriptase-PCR and immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 36 publications
(93 reference statements)
5
54
0
1
Order By: Relevance
“…A recent study demonstrated that siRNA-mediated knockdown of K + channels of the Shaker (Kv1) family effectively supports the survival of axotomized RGCs. 36 This approach is substantially more specific than common, nonselective channel blockers.…”
Section: Inhibition Of Apoptotic Pathways and Manipulation Of Mitochomentioning
confidence: 99%
“…A recent study demonstrated that siRNA-mediated knockdown of K + channels of the Shaker (Kv1) family effectively supports the survival of axotomized RGCs. 36 This approach is substantially more specific than common, nonselective channel blockers.…”
Section: Inhibition Of Apoptotic Pathways and Manipulation Of Mitochomentioning
confidence: 99%
“…The high tropism of Adeno-Associated Virus (AAV) vectors is beneficial to target RGCs, with an infection rate approaching 90% of cells near the injection site 6,7,[13][14][15] . Moreover, RGCs can be selectively transfected by applying siRNAs, plasmids, or viral vectors to the cut end of the optic nerve [16][17][18][19] or injecting vectors into their target the superior colliculus 10 . This allows researchers to study apoptotic mechanisms in the injured neuronal population without confounding effects on other bystander neurons or surrounding glia.…”
mentioning
confidence: 99%
“…It has also been shown that proapoptotic and apototic related proteins can activate voltage-gated K, Na, Ca and anion channels directly (Ekhterae et al., 2001; Koeberle et al, 2010;Platoshyn et al, 2002;Storey et al, 2003;Vander Heiden et al, 2001;Yao et al, 2011).…”
Section: Plasma Membrane-bound Voltage-gated Ion Channels Are Importamentioning
confidence: 99%
“…Altered composition of ions has been reported to directly affect activation of proteins involved in apoptosis (cytochrome c, proteases, nucleases etc), as well as formation of the apoptosome, affecting the ratio between pro-and antiapoptotic proteins Hampton et al, 1998;Hughes et al, 1997;Karki et al, 2007;Koeberle et al, 2010;Strickland et al, 1991;Thompson et al, 2001;Wondrak et al, 1991).…”
Section: Plasma Membrane-bound Voltage-gated Ion Channels Are Importamentioning
confidence: 99%